Impact of chronic methamphetamine treatment on the atherosclerosis formation in ApoE−/− mice fed a high cholesterol diet - Zhu, Pengfei (Oncotarget, 2017)
BACKGROUND: We previously reported that methamphetamine could promote atherosclerosis (AS) in ApoE−/− mice fed normal chow. We herein observed the impact of methamphetamine on AS in ApoE−/− mice fed a high cholesterol diet and explored the potential mechanisms. RESULTS AND MATERIALS AND METHODS: Male ApoE−/− mice fed a high cholesterol diet were treated with saline (NS, n = 5) or methamphetamine [8 mg/kg/day (M8, n = 6) through intraperitoneal injection] for 24 weeks. Afterwards, the percentage area of atheromatous plaque in aortic root (44.31 ± 3.21% vs. 32.91 ± 3.58%, P < 0.01) and atherosclerotic lesion area on Oil red O stained en face aorta (32.74 ± 6.97% vs. 18.72 ± 3.65%, P < 0.01) were significantly higher in M8 group than in NS group. The percentages of Th1 cells and Th17 cells in spleen were significantly higher while the percentages of Th2 cells and CD4(+)CD25(+)Foxp3(+) Tregs were significantly lower in M8 group than in NS group. mRNA expressions of TNF-α, IFN-γ, and IL-17 were significantly up-regulated, IL-4, IL-10, Foxp3, and TGF-β were significantly down-regulated in carotid artery and in spleen in M8 group compared to NS group. CONCLUSIONS: Chronic methamphetamine treatment can enhance atherosclerotic plaque formation possibly through promoting proinflammatory cytokine secretions in ApoE−/− mice fed a high cholesterol diet.